The Effectiveness Of Fear Of Missing Out (FOMO) Based Digital Marketing Strategy In Increasing The Attractiveness Of Enola Coffee Shop To Generation Z - Moh Dhiya Ulhaq; Ponirin Ponirin; Umar Syarifaddin; Faruq Lamusa (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
This study aims to evaluate the effectiveness of Fear of Missing Out (FOMO)-based digital marketing strategies in increasing the attractiveness of Enola Coffee Shop to Generation Z. With the increasing use of social media, FOMO-based marketing strategies are becoming increasingly relevant in building customer awareness and increasing visits to coffee shops. This research uses a qualitative approach with an in-depth interview method to several respondents who are customers of Coffee Shop Enola. The results showed that most customers were aware of the promotions carried out by Coffee Shop Enola through digital platforms such as Instagram and TikTok. The types of promotions that attract the most attention are limited-time discounts, exclusive events, and collaborations with other brands. In addition, customers' emotional responses to the FOMO strategy varied; some felt enthusiastic and compelled to visit the coffee shop immediately, while others preferred the convenience of the place compared to the urgency of the promotion. The study also found that FOMO strategies contribute to increasing word-of-mouth marketing, where customers actively share promotions with their friends. Although the FOMO strategy has proven to be effective in increasing the attractiveness of Coffee Shop Enola, there are still some aspects that need to be improved, such as exploration of promotions on TikTok, transparency of information regarding menu availability, and development of customer loyalty programs. Therefore, Coffee Shop Enola needs to develop a more adaptive and sustainable digital marketing strategy to increase customer loyalty in the long run. Thus, the FOMO strategy is not only an effective marketing tool, but also contributes to building emotional attachment between customers and brands.